Does the limb lengthening reduce the incidence of hip dislocation in patients with neurological disorders and insufficient muscle tension who undergoing hip arthroplasty? - Li, ZiHang; Chu, Kun; Yang, Meng; Liu, SiKai; Liu, Bo; Li, HuiJie (Frontiers in Surgery, 2024)
Background The soft-tissue tension is closely associated with postoperative hip dislocation in patients undergoing total hip arthroplasty (THA), especially for those patients with neurological disorders and insufficient muscle tension. The aim of this study is to explore the effect of limb lengthening on the incidence of complications following THA in patients with neurological disorders and insufficient muscle tension. Methods This retrospective analysis examines individuals with neurological disorders, such as ischemic stroke and poliomyelitis, who underwent primary total hip arthroplasty (THA) at our medical center between January 2015 and April 2021. Demographic and baseline characteristics (such as age, gender, muscle strength) were obtained from medical records. The limb length, offset and the positional parameters of both acetabular and femoral component were measured on pre- and postoperative plain radiograph. The primary outcome was the occurrence of hip dislocation. The secondary outcome included the incidence of other complications and the hip function (determined by Harris score). The correlation between the occurrence of hip dislocation and limb lengthening was analyzed. Results A total of 258 patients were finally analyzed. The hip dislocations were identified in 35 patients (overall incidence=13.57%). The incidence of early dislocation was lower in patients whose limb-length discrepancy (LLD) was over 20mm (incidence=4.1% for LLD >20mm, 12.2% for LLD 10mm-20mm and 17% for LLD <10mm). The odds ratio (OR) was 0.206 and 95% confidence interval (CI) was 0.058–0.737 (compared between LLD <10mm and LLD >20mm). But the no difference was identified regarding on the incidence of late dislocation among patients with different LLD. Moreover, the overall incidence of other complications was elevated in patients with LLD >20mm (incidence=17.58% for LLD >20mm, 11.11% for LLD 10mm-20mm and 3.19% for LLD <10mm; OR=6.464, 95%CI=1.768-23.640). And the Harris scores, which reflected the hip function, was gradually decreased with the increasing in LLD. Different from that of LDD, the incidences of other complications were similar among patients with different offset discrepancy. Conclusion Femoral stem with lower cervico-diaphyseal angle (higher offset) should be recommended to patients with neurological disorders who were in high risk of postoperative dislocation. Isolated increasing in limb length should be avoided.